2020
DOI: 10.1007/s42770-020-00253-w
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acetylation as drug target in fungi: an underexplored potential in Aspergillus spp.

Abstract: In recent years, the intensification of the use of immunosuppressive therapies has increased the incidence of invasive infections caused by opportunistic fungi. Considering that, the spread of azole resistance and amphotericin B (AmB) inefficiency against some clinical and environmental isolates has been described. Thus, to avoid a global problem when controlling fungal infections and critical failures in medicine, and food security, new approaches for drug target identification and for the development of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 138 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…Majority of eukaryotic proteins undergo reversible post-translational modifications (PTM) that enable them to gain their final activity. These processes include acetylation, methylation, phosphorylation, glycosylation, and ubiquitination of protein molecules (Wassano et al 2020 ). Reversible PTMs control various cell processes via regulation of protein function, the most important modification is acetylation of proteins that regulates translation, gene expression, and metabolism (Kuchler et al 2016 ).…”
Section: Aminoacyl-trna Synthetasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of eukaryotic proteins undergo reversible post-translational modifications (PTM) that enable them to gain their final activity. These processes include acetylation, methylation, phosphorylation, glycosylation, and ubiquitination of protein molecules (Wassano et al 2020 ). Reversible PTMs control various cell processes via regulation of protein function, the most important modification is acetylation of proteins that regulates translation, gene expression, and metabolism (Kuchler et al 2016 ).…”
Section: Aminoacyl-trna Synthetasesmentioning
confidence: 99%
“…Acetylation is an evolutionarily conserved process that involves acetyltransferase enzymes transmitting the acetyl group from a donor acetyl coenzyme A (CoA) to a suitable acceptor molecule. Histone acetyltransferases EC 2.3.1.48 (HATs) and histone deacetylases EC 3.5.1.98 (HADC) catalyze, respectively, the addition or removal of acetyl groups to or from lysine residues, most importantly in histone proteins, and have been identified as potential drug targets (Wassano et al 2020 ). It was revealed that HAT/ HADC activities are required for C. albicans virulence.…”
Section: Aminoacyl-trna Synthetasesmentioning
confidence: 99%
“…Currently, several KAT and KDAC inhibitors have been developed for the treatment of fungal infections in humans. For example, nicotinamide is widely used as an overall sirtuin inhibitor (Avalos et al ., 2005), which strongly suppresses the growth of various pathogenic fungi, such as Candida albicans , Candida krusei , Aspergillus fumigatus and Aspergillus nidulans (Wurtele et al ., 2010; Wassano et al ., 2020). In addition, anacardic acid (6‐pentadecylsalicylic acid), a KAT inhibitor that inhibits p300, PCAF and Tip60, also affects the mycelial growth and conidial germination of the plant‐pathogenic fungus M. oryzae (Muzaffar et al ., 2016).…”
Section: Perspectivesmentioning
confidence: 99%
“…Post-translational modifications (PTMs) have also attracted attention because of their vital roles in fungal growth, virulence, stress responses, and drug resistance (20,21). Increasing evidence indicates that PTMs, especially acetylation, contribute to the development of drug resistance in different fungi (22,23). However, no study has considered the role of PTMs in the development of drug resistance in C. krusei.…”
Section: Introductionmentioning
confidence: 99%